Bicyclo[6.1.0]nonyne and tetrazine amino acids for Diels–Alder reactions. Issue 70 (15th September 2017) - Li, Xu; Liu, Zhengkun; Dong, Shouliang
Abstract : Here we report a general method for the de novo synthesis of a bicyclo[6.1.0]nonyne group containing an amino acid, and used Marfey's reagent for chiral analysis. Abstract : Here we report a general method for the de novo synthesis of a bicyclo[6.1.0]nonyne group containing an amino acid, and used Marfey's reagent for chiral analysis. This unnatural amino acid offered exceptional reactivity in the inverse electron demand Diels–Alder cycloaddition with tetrazine containing amino acids. The subsequent selective labeling of living cells at low dye concentrations demonstrated the usefulness of the new amino acid for future imaging studies. This work also laid the foundation for introducing this unnatural amino acid into peptides based on the solid-phase synthesis method.